Equity derivatives explained - Bouzoubaa, Mohamed; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
A succinct book that provides readers with all they need to know about the equity derivatives business. It deals with vanilla equity products, their usage, structuring and their risk management. The author efficiently bridges the gap between theory and practice, constantly linking risk management tools with specific business objectives.
Keywords: Derivative securities; Options (Finance).